Тенденції та перспективи ринку логістичних послуг України - Чорнописька, Н. В.; Шандрівська, О. Є. (Видавництво Львівської політехніки, 2012)
Узагальнено стан розвитку ринку логістичних послуг, здійснено порівняння основних тенденцій розвитку цього ринку в Україні та Європі. Запропоновано поділ вітчизняного ринку логістичних послуг на п’ять сегментів, а саме: транспортно-експедиційні послуги, професійні складські послуги, експрес-доставка, контрактна логістика, управління ланцюгами поставок. Проаналізовано динаміку розвитку сегменту професійних складських послуг за 2006–2011 рр. Досліджено структуру сегменту контрактної логістики: суперництво між конкуруючими фірмами; сили впливу постачальників; сили впливу споживачів; конкуренцію з боку товарів-субститутів та бар’єри входу у галузь. Виявлено ключові чинники успіху, окреслено перспективи та привабливість контрактної логістики в Україні. The state of the logistics services market are summarized in the article. Сomparison of the main trends in this market in Ukraine and Europe is shown. Division of the domestic market of logistics services into five segments, namely: freight forwarding services, professional warehousing services, express delivery, contract logistics, supply chain management is proposed. Dynamics of the segment of professional warehousing services for 2006-2011 are analyzed. The structure of demand, new supply, main facts and specific development in the capital and regionals Ukraine is show. The structure of segment contract logistics is invastigated: the rivalry between competing firms, the impact of suppliers force; forces of consumers influence, competition from goods-substitutes and barriers to entry into the sector. Main drivers contract logistics development are: development of international trade, retail operators activities and development of on-line trade. Key success factors are discovered. Prospects and the attractiveness of contract logistics in Ukraine are determined.
Trends and perspectives of logistics services market of Ukraine
Keywords: ринок логістичних послуг; контрактна логістика; професійні складські послуги; логістичні оператори; market of logistics services; contract logistics; professional warehousing services; logistics operators